Costs and health-related quality of life in relation to caries - Lisa Kastenbom; Alexandra Falsen; Pernilla Larsson; Karin Sunnegårdh-Grönberg; Thomas Davidson (BMC, 2019)
Abstract Background Dental caries remains a common and expensive disease for both society and affected individuals. Furthermore, caries often affect individuals' health-related quality of life (HRQoL). Health economic evaluations are needed to understand how to efficiently distribute dental care resources. This study aims to evaluate treatment costs and QALY weights for caries active and inactive adult individuals, and to test whether the generic instrument EQ-5D-5 L can distinguish differences in this population. Methods A total of 1200 randomly selected individuals from dental clinics in Västerbotten County, Sweden, were invited to participate. Of these, 79 caries active and 179 caries inactive patients agreed to participate (response rate of 21.7%). Inclusion criteria were participants between 20 and 65 years old and same caries risk group categorization in two consecutive check-ups between 2014 and 2017. Results Treatment costs showed to be twice as high in the caries active group compared to the caries inactive group and were three times higher in the caries active age group 20-29 compared to the caries inactive age group 20-29. Differences between the groups was found for number of intact teeth according to age groups. In the EQ-5D-5 L instrument, more problems relating to the dimension anxiety/depression was seen in the caries active group. QALY weights showed tendencies (non-significant) to be lower in the caries active group. Conclusions These findings highlight the need for efficient treatments and prevention strategies as well as adequate money allocation within dentistry. However, further research is needed to assess appropriate instruments for health economic evaluations.